2021
DOI: 10.3390/app11093746
|View full text |Cite
|
Sign up to set email alerts
|

Isatin-Hydrazones with Multiple Receptor Tyrosine Kinases (RTKs) Inhibitory Activity and In-Silico Binding Mechanism

Abstract: Recently, we have reported a series of isatin hydrazone, two of them, namely, 3-((2,6-dichlorobenzylidene)hydrazono)indolin-2-one (1) and 3-((2-chloro-6-fluorobenzylidene)hydrazono)indolin-2-one (2) having potent cytotoxicity, showing cyclin-dependent kinases (CDK2) inhibitory activity and bearing recommended drug likeness properties. Since both compounds (1 and 2) showed inhibitory activity against CDK2, we assumed it would also have multiple receptor tyrosine kinases (RTKs) inhibitory activity. Considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Among the discovery of novel scaffolds with multiple kinase inhibitory activities versus various kinases, including FLT3 kinase, Al-Salem et al in 2021 synthesized many oxindole-based derivatives with versatile kinase inhibitory activity, specifically, compound 17 [ 87 ]. Compound 17 showed circumvention of different tyrosine kinases, including CDK-2 with IC 50 equal to 0.301 µM, which was about half the threshold lower than recognized kinase inhibitor imatinib with IC 50 equal to 0.131 µM and comparable to the primary FLT-3 hampering agent Sunitinib with IC 50 equal to 0.262, and versus EGFR, VEGFR-2 (KDR), and FLT-3 with IC 50 s equal to 0.369, 0.266, and 0.546 µM, respectively ( Table 3 ) .…”
Section: Oxindole Based Flt3 Inhibitorsmentioning
confidence: 99%
“…Among the discovery of novel scaffolds with multiple kinase inhibitory activities versus various kinases, including FLT3 kinase, Al-Salem et al in 2021 synthesized many oxindole-based derivatives with versatile kinase inhibitory activity, specifically, compound 17 [ 87 ]. Compound 17 showed circumvention of different tyrosine kinases, including CDK-2 with IC 50 equal to 0.301 µM, which was about half the threshold lower than recognized kinase inhibitor imatinib with IC 50 equal to 0.131 µM and comparable to the primary FLT-3 hampering agent Sunitinib with IC 50 equal to 0.262, and versus EGFR, VEGFR-2 (KDR), and FLT-3 with IC 50 s equal to 0.369, 0.266, and 0.546 µM, respectively ( Table 3 ) .…”
Section: Oxindole Based Flt3 Inhibitorsmentioning
confidence: 99%
“…Literature surveys have shown isatin scaffold as an anticancer agent against various human tumor cell lines, especially the tyrosine kinase inhibitor ( 10 11 12 13 ). The analogs of isatin such as sunitinib were exposed to tyrosine kinase inhibitory properties ( 10 14 ) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Salem et al . reported isatin-hydrazones as multiple receptor tyrosine kinase inhibitors ( 13 ) ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the FDA’s approval of the VEGFR-2 inhibitor Sunitinib, medicinal chemists have paid special attention to the identification of new isatin-based anti-cancer candidates targeting VEGFR-2 kinase [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Our research team has recently reported several VEGFR-2 inhibitors based on the isatin scaffold [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%